Long-term thermal sensitivity of Earth’s tropical forests - Sullivan, M.J.P.; Lewis, S.L.; Affum-Baffoe, K.; Castilho, C.; Costa, F.; Sánchez, A.C.; Ewango, C.E.N.; Hubau, W.; Marimon, B.; Monteagudo Mendoza, Abel L.; Qie, L.; Sonké, B.; et al. (American Association for the Advancement of Science, 2020)
A key uncertainty in climate change models is the thermal sensitivity of tropical forests and how this value might influence carbon fluxes. Sullivan et al. measured carbon stocks and fluxes in permanent forest plots distributed globally. This synthesis of plot networks across climatic and biogeographic gradients shows that forest thermal sensitivity is dominated by high daytime temperatures. This extreme condition depresses growth rates and shortens the time that carbon resides in the ecosystem by killing trees under hot, dry conditions. The effect of temperature is worse above 32°C, and a greater magnitude of climate change thus risks greater loss of tropical forest carbon stocks. Nevertheless, forest carbon stocks are likely to remain higher under moderate climate change if they are protected from direct impacts such as clearance, logging, or fires.Science , this issue p. 869